Disappearance of Kersting's groundnut (Macrotyloma geocarpum (Harechal and Baudet) in soth-western Nigeria: an indicator of genetic erosion - Amujoyegbe, B.J.=700 1 Obisesan, I.O.; Ajayi, A.O.
(Es, En, Pt)
ilus., 16 ref.
Keywords: MACROTYLOMA; PERDIDAS POR MANIPULACION; GRANOS; MANO DE OBRA; EROSION; DEFICIT; RENDIMIENTO; NIGERIA; DESAPARICION DE GRANO; NOTICIARIO DE RECURSOS FITOGENETICOS